Pengaruh Online Customer Review dan Online Customer Rating Terhadap Loyalitas Konsumen Burger Bangor di Shopeefood Yogyakarta - sukma novita setyaningrum; Putra Prasetya, Bangun (Transformasi: Journal of Economics and Business Management, 2024)
Abstract. Digital transformation has brought about changes in shopping patterns with the advent of online shopping and food ordering. Reviews and ratings have a big impact on consumer preferences, so it is important to pay attention to reviews and ratings in online marketing strategies. This study aims to measure the impact of online consumer reviews and ratings on consumer loyalty to Bangor Burger on ShopeeFood. Through a quantitative approach, the sample was taken using the Non - probability sampling method with a total of 100 respondents. The population studied was consumers who had bought Bangor Burger at ShopeeFood. Data was collected through questionnaires distributed to respondents. Data analysis was carried out using path analysis with IBM SPSS software. The results showed that reviews and ratings have a significant influence on Burger Bangor consumer loyalty at ShopeeFood. Keywords: Online Shopping, ShoppeeFood, Burger Bangor, Consumers, Review, Rating, Consumer Loyalty. Abstrak. Transformasi digital telah membawa perubahan dalam pola belanja dengan hadirnya belanja online maupun pemesanan makanan. Review dan rating memiliki dampak yang besar pada preferensi konsumen, sehingga penting untuk memperhatikan review dan rating dalam strategi pemasaran online. Penelitian ini bertujuan untuk mengukur dampak review dan rating konsumen secara online terhadap loyalitas konsumen pada Burger Bangor di ShopeeFood. Melalui pendekatan kuantitatif, sampel diambil menggunakan metode Non – probability sampling dengan jumlah responden sebanyak 100 responden. Populasi yang diteliti adalah konsumen yang pernah membeli Burger Bangor di ShopeeFood. Data dikumpulkan melalui kuesioner yang disebarkan kepada responden. Analisis data dilakukan menggunakan path analysis dengan perangkat lunak IBM SPSS. Hasil penelitian menunjukkan bahwa review dan rating memiliki pengaruh signifikan terhadap loyalitas konsumen Burger Bangor di ShopeeFood. Kata kunci: Belanja Online, ShoppeeFood, Burger Bangor, Konsumen, Review, Rating, Loyalitas Konsumen.